Hierarchical PFAMs annotated within nodules of the actinorhizal hosts Datisca glomerata and Ceanothus thyrsiflorus. - Marco Guedes Salgado (Stockholm University, 2018)
Averaged Transcript per Million reads (TPM) covering the Top 100 contigs assigned within the “biological process” category of Datisca glomerata and Ceanothus thyrsiflorus.
Keywords: Computational Biology; 60705 Plant Physiology; Biological Sciences; Biologi; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)